Future Living Arrangement for Aging Parents and Its Associated Factors - Setiyani, Rahmi; Sumarwati, Made; Ramawati, Dian (Jurusan Keperawatan FIKES UNSOED, 2019)
Background: Shift in demographic structure in Indonesia has raised concern over number of issues, including change in living arrangement of older people. Objectives: The purpose of this study is to examine adult children’s choice of future living arrangement for elderly parent and its associated factors. Methods: A cross sectional study was conducted among 300 young adults in Central Java, Indonesia. Descriptive statistics, Chi-Square and Fisher exact test were used to analyze the data. Results: Majority of respondents (97.3%) preferred parents to live at home, in multi-generational household with children and/or grandchildren (84.5%) in their old age. The choice was significantly influenced by children gender, marital status of parent, and family type (p=0.00; p=0.05, and p=0.05 respectively). Conclusions: In certain circumstances, living in multigenerational household still became a favorable option of living arrangement for elderly parents. Children gender, parent’s marital status and family type were likely to influence the choice. Further researches are needed to investigate which best living arrangement that support older people well-being.